Current Challenges in Efficient Lithium‐Ion Batteries' Recycling: A Perspective. Issue 12 (8th September 2022) - Yu, Xiaolu; Li, Weikang; Gupta, Varun; Gao, Hongpeng; Tran, Duc; Sarwar, Shatila; Chen, Zheng
Abstract: Li‐ion battery (LIB) recycling has become an urgent need with rapid prospering of the electric vehicle (EV) industry, which has caused a shortage of material resources and led to an increasing amount of retired batteries. However, the global LIB recycling effort is hampered by various factors such as insufficient logistics, regulation, and technology readiness. Here, the challenges associated with LIB recycling and their possible solutions are summarized. Different aspects such as recycling/upcycling techniques, worldwide government policies, and the economic and environmental impacts are discussed, along with some practical suggestions to overcome these challenges for a promising circular economy for LIB materials. Some potential strategies are proposed to convert such challenges into opportunities to maintain the global expansion of the EV and other LIB‐dependent industries. Abstract : Rapid prospering of the electric vehicle industries makes Li‐ion batteries (LIBs) recycling an urgent need. However, the global LIB recycling effort is hampered by various challenges, including recycling/upcycling techniques, global government policies, and economic and environmental implications. Specific challenges are summarized along with some practical suggestions to overcome these challenges for a promising circular economy for LIB materials.